Causes and consequences of spreading populism: How to deal with this challenge - Sergej Guriev (EconPol Forum, 2024)
We live in the era of the unprecedented rise of populism - measured either by voting share for populist (i.e., antielite and anti-pluralist) politicians or by the presence of populists in governments. There is convincing evidence that the rise of populism has been caused by secular trends (globalization, automation, and the rise of social media) as well as one-off events (such as the 2008-2009 global financial crisis and subsequent austerity and the 2015-2016 refugee crisis). It is also plausible that the rise of populism is a response to cultural wars. There is also evidence that shows that populists in power slow down economic growth and undermine democratic political institutions. There is limited research on solutions to the problem of the rise of populism. The suggested solutions include redistribution, regulating social media, deliberative democracy, and ranked-choice voting.
Keywords: 330